Nie-ludzkie doświadczenie i jego ślady w kobiecych autobiografiach. Przypadek trzech modernistek - Pańczak, Martyna (Studia Europaea Gnesnensia, 2018)
The article discusses the possibility of reading women’s autobiographies with the main focus on the lives non-human animals. Drawing on the theory of autobiography and the field of animal studies I argue that it is feasible to extract valid and accurate accounts of numerous human-animal relationships or find traces of various animal experience whereby animals can be recognized as agents and subjects.